An Overview of Pregnant Women’s Knowledge Regarding Exclusive Breastfeeding at the Dadok Tunggul Hitam Community Health Center, Padang City - Hendri Devita; Indrawati Indrawati; Annisa Wahyuni; Nirmala Sari; Putri Engla Pasalina (International Journal of Health and Medicine, 2026)
Despite national efforts to promote exclusive breastfeeding, its coverage in Indonesia, including in Padang City, has not yet reached the national target of 80%. One of the factors contributing to this gap is the insufficient knowledge of pregnant women regarding exclusive breastfeeding. Therefore, this study sought to assess the level of knowledge among pregnant women concerning exclusive breastfeeding at the Dadok Tunggul Hitam Community Health Center in Padang City. A descriptive quantitative approach was employed involving 47 first-trimester pregnant women selected through simple random sampling from a population of 88 individuals. Data were gathered using a structured closed-ended questionnaire that assessed respondents’ knowledge of the definition, benefits, classification, and proper breastfeeding techniques, and were analyzed using frequency distributions. The findings indicated that more than half of the respondents (51.1%) demonstrated a high overall level of knowledge, while 42.6% had a moderate level and 6.4% had a low level. In terms of specific domains, knowledge of the definition of exclusive breastfeeding was predominantly moderate (44.7%), knowledge of its benefits was evenly distributed between the high and moderate categories (42.6% each), whereas knowledge of breastfeeding classification and proper breastfeeding techniques was mainly at the moderate level (46.8% each). These findings suggest that although the overall knowledge of exclusive breastfeeding among pregnant women was generally satisfactory, important knowledge gaps remain, particularly concerning breastfeeding classification and appropriate breastfeeding techniques. Strengthening health education programs through regular counseling sessions and the use of engaging visual educational media may help improve both knowledge and breastfeeding practices among pregnant women